Penentuan Parameter Model NRECA Untuk Debit Pada DAS Temef - Krisnayanti, Denik Sri; Chandra, Chrystin; Bunganaen, Wilhelmus; Udiana, I Made; Damayanti, Alvine Cinta (Department of Civil Engineering, Diponegoro University, 2022)
A watershed in which the observed discharge data is not available or incomplete becomes a problem in thewater utilization projects. Observation discharge data obtained from Pos Duga Air Sungai Temef is less reliable because the measurement of water level data for the last few years has been carried out by direct observation without using a discharge measuring device. Obtain river discharge data, it can be done by simulating rainfall data into discharge data, one of them is NRECA Model. In NRECA Model, there are several parameters, namely index soil moisture capacity (nominal), Percent Sub Surface (PSUB), Ground Water Flow (GWF), and crop coefficient (kc). Determination of the parameters NRECA Model was obtained by trial and error based on the value limit so that the coefficient correlation (r) between observation discharge and simulation discharge was close to 1. The values used for the index soil moisture capacity (nominal), percent sub surface (PSUB), ground water flow (GWF), and crop coefficient (kc) are 0,20; 0,85; 0,50; and 0,60.